Statistical Approximation Operators - Jassim, Sahib K.; AbdulNaby, Zainab I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we obtain some statistical approximation results for a general class of maxproduct operators including the paused linear positive operators.